Simple water vapor sampling for stable isotope analysis using affordable valves and bags - A. Dahlmann; A. Dahlmann; J. D. Marshall; D. Dubbert; M. Hoffmann; M. Dubbert (Atmospheric Measurement Techniques)
Water-stable isotopes are commonly used in hydrological and ecological research. Until now, most measurements of soil or plant water isotopes have been made by taking a sample from the field and extracting its water in the laboratory. More recently, samples have been collected with gas-permeable membranes (GPMs) and measured in the field. These new methods, however, present challenges in achieving high-resolution measurements across multiple sites since they require significant effort and resources. Gas bag sampling offers the advantage of non-destructive, cost-efficient, easy-to-perform measurements without the need to bring a cavity ring-down spectroscopy (CRDS) analyzer into the field. We used gas-permeable membranes to extract samples of water vapor from the soil, which were then stored in multi-layer foil bags until analysis. The bags were modified with homemade connections to reduce leakage and simplify gas transfers. The bags were tested using laboratory standards to determine their maximum storage time, potential memory effects, and reusability. The storage experiment with new bags demonstrated the ability to store water vapor samples for up to 7 d while maintaining mostly acceptable trueness for δ2H and acceptable to questionable trueness for δ18O. Trueness was defined as the mean difference between the measured and known water vapor placed into the bags and precision by the standard deviation of replicate measurements. The memory experiment using new bags revealed that the influence of previous samples increased with duration of storage. In both experiments, the light standards seemed to result in less accuracy. The reuse experiment confirmed that the bags can be filled repeatedly, provided they are used for similar sample lines and flushed 10 times with dry air. To demonstrate bag applicability in the field, we compared measurements of stored samples to measurements made directly in the field. Storing beyond 24 h needs further investigation but appears promising. With new gas bags up to 24 h of storage, we found accuracies of 0.2 ‰ ± 0.9 for δ18O and 0.7 ‰ ± 2.3 for δ2H. When the bags were reused and stored up to 24 h, they yielded accuracies of 0.1 ‰ ± 0.8 for δ18O and 1.4 ‰ ± 3.3 for δ2H. The proposed system is simple, cost-efficient, and versatile for both lab and field applications; however, case-specific testing is necessary given the remaining uncertainties.